Glomus Tumor: "A-Not-So-Rare" Cause of Chronic Shoulder Pain—A Case Report and Literature Review. (27th May 2021) - Vieira, Luís; Pereira, Pedro; Nunes, Bernardo; Matos, Rui; Sousa, António; da Silva, Manuel Ribeiro
Abstract : Case . A 61-year-old male presented with chronic shoulder pain resistant to conservative treatment. Imaging identified a nodular lesion in the deltoid muscle, which histology after resection identified as a glomus tumor. After surgery, the patient became asymptomatic and at 4-year follow-up has not shown signs of recurrence. Conclusion . Glomus tumors around the shoulder should be considered when investigating chronic shoulder pain, as they are more common than thought. Despite being elusive, when diagnosed, excellent outcomes may be expected, with surgery resection being curative.